Variations in Stable Carbon Isotope Composition and Leaf Traits of Picea schrenkiana var. tianschanica along an Altitude Gradient in Tianshan Mountains, Northwest China - Huiwen Zhang; Jianying Ma; Wei Sun; Fahu Chen (The Scientific World Journal)
To understand the morphological and physiological responses of leaves to changes in altitudinal gradients, we examined ten morphological and physiological characteristics in one-year-old needles of Picea schrenkiana var. tianschanica at ten points along an altitudinal gradient from 1420 to 2300 m a.s.l. on the northern slopes of the Tianshan Mountains in northwest China. Our results indicated that LA, SD, LPC, and LKC increased linearly with increasing elevation, whereas leaf δ13C, LNC, Chla + b, LDMC, LMA, and Narea varied nonlinearly with changes in altitude. With elevation below 2100 m, LNC, Narea, and Chla + b increased, while LDMC and LMA decreased with increasing altitude. When altitude was above 2100 m, these properties showed the opposite patterns. Leaf δ13C was positively correlated with Narea and LNC and negatively correlated with SD and LA, suggesting that leaf δ13C was indirectly controlled by physiological and morphological adjustments along altitudinal gradients. Based on the observed maximum values in LNC, Narea, Chla + b, and LA and the minimum values in LMA and LDMC at the elevation of 2100 m, suggesting higher photosynthetic capacity and greater potential for fast growth under superior optimum zone, we concluded that the best growing elevation for P. schrenkiana var. tianschanica in the Tianshan Mountains was approximately 2100 m.